PERSEPSI PETANI TERHADAP KEBIJAKAN PENGEMBANGAN AGRIBISNIS TANAMAN BAWANG MERAH DI KELURAHAN BANTURUNG KECAMATAN BUKIT BATU KOTA PALANGKA RAYA - Roky Mandaraga; Revi Sunaryati; Eka Nor Taufik (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2019)
This research was conducted to find out how big the level of farmers' perceptions of the onion agribusiness development policy. The author uses a Likert scale for the basis of calculations. This research was conducted in Banturung Village, Bukit Batu Subdistrict, Palangka Raya City. The results of the study consisted of: in terms of program assistance in the "strongly agree" category where the farmers' desire for assistance is very large so that farmers better understand the program this assistance is running. In terms of preparation of seeds and input in the category of ?strongly agree" where the great expectations of farmers for the preparation of seeds and production inputs have great benefits and contributions. In terms of technical assistance for cultivation and post harvest through extension workers in the "strongly agree" category where the role of extension agents is very large for government policy regarding the development of this onion plant agribusiness. In terms of preparation of land processing tools, post harvest tools, and results processing tools. In the category "strongly agree" where the use of tools in the agricultural production process has a large contribution to achieving its effectiveness optimally. In terms of seed propagation, seed purification and seed warehouse in the "strongly agree" category where to reduce the initial production capital, the farmer can increase his own seeds. The hope is that every affected farmer gets this program to get his own seed warehouse. In terms of the implementation of disease control in the category "strongly agree" where the control of pest disease is expected to have a large contribution to the cultivation activities carried out.